Estudio agro socioeconómico y alternativas tecnológicas para el desarrollo rural del sector Barbones - Álvarez, Miguel (2005)
This research was carried out in the sector of Barbones that belongs to the parish of El Guabo of El Oro province. The objectives were: 1. To study the social structure of the peasant family, workforce and emigra-tion 2. To determine the parameters related to the agricultural produc-tion (agro systems) technology and productivity. 3. To propose in base to the available resources, alternative of production and to develop agricultural techniques from Barbones. It was polled to 30 farmers, in a sample stratified for the sites: Sta. Lucía, Sabaducal, Paraiso, So-ledad, La Raquel, 10 de Agosto, and Barbones. The results establish that, the average of the number of members of the families is of 4,7; also it is demonstrated that the migration affects to the site La Raquel in 18,0 % within men and women. The cultural practice that favor to the crop, and that for the most part it is a manual activity that it does not exceed of 2 salaries in average. The productivity of the studied sites is between 38,6 and 25 boxes/ha, considering that these planta-tions are organic and traditional. The 80,8 % of the farmers in average sell their product to the Association of small producing of El Guabo, it is evident also to emphasize the technical assistance offered in most of the sites by this association, also it is notable the few governmental institutions collaboration that little to nothing make for the develop-ment of the small farmers of this sector. To comply with one objec-tive, it can be recommend as very relevant to the technical staff of the Association of El Guabo to follow advising and incentivating to the small farmers to the use and application of organic products.